External shocks, trade margins, and macroeconomic dynamics - Stefano D'Addona; Lilia Cavallari (Economies, 2020)
This paper studies the role of the exchange rate regime for trade of new products. It first provides VAR evidence that a rise in external productivity shifts trade away from new products and more so in fixed regimes. Then, it presents a model with firm dynamics in line with this evidence. We argue that exchange rate policy can affect firms' entry decisions with consequences for the competitiveness of a country's exports well beyond the short run. In our setup, fixed exchange rates can foster the competitiveness of firms that trade new products, while flexible rates favor firms that produce mature products.
Keywords: E31; E32; E52; F10; F44; 330; comparative advantage; dsge model; exchange rate policy; firm entry; international business cycle; panel var; trade margins